A novel damage index for online monitoring of RC slabs under monotonic loading by integration of process controlling into acoustic emission technique - Behnia, Arash; Chai, Hwa Kian; Mousa, Ahmad A.; Ravanfar, Seyed Alireza (Elsevier, 2019)
This study introduces a novel structural health monitoring scheme for cementitious composite slabs with the aid of acoustic emission (AE) technique coupled with statistical process controlling (SPC) method. The adopted framework is an integrated monitoring solution that effectively relates current state (damaged) to reference state of the structure. Evaluation of the latter was made possible using autoregressive model incorporating a set of damage-sensitive feature. In order to provide a benchmark damage indicator, the collected data were processed using control chart analysis. The damage indicators for the former was similarly obtained and then compared with the benchmark to gauge the structural damage. These control charts offer a robust framework meticulously identifying inconsistency in the damage-sensitive feature imposed over the monitoring period. Linear and quadratic projections were also incorporated into SPC model to enhance identification of system transition to other damage states.